Structure and properties of montmorillonite containing Ca2+, Sr2+, and Ba2+ cations simultaneously; Journal of Molecular Liquids; Vol. 382 - Wang Cailun; Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Bespala E. V. Evgeniy (Evgeny) Vladimirovich; Poberezhnikov A. D. Andrey Dmitrievich; Baraban A. P. Aleksandr Petrovich; Shukshina D. D. Darjya Dmitrievna; Semenov D. A. Dmitry Andreevich (2023, 2023)
Title screen